Compelling Increase in Parvovirus B19 Infections: Analysis of Molecular Diagnostic Trends (2019–2024) - Flora Marzia Liotti; Simona Marchetti; Sara D’Onghia; Lucio Romano; Rosalba Ricci; Maurizio Sanguinetti; Rosaria Santangelo; Brunella Posteraro (Viruses)
Human parvovirus B19 (B19V) follows a well-documented cyclical epidemiology, with peaks occurring every 3–4 years. However, recent reports indicate an unusual resurgence in B19V infections across multiple countries, prompting increased surveillance. This study analyzed molecular diagnostic assay results from 826 unique-patient samples tested for B19V DNA between 2019 and 2024 at a large Italian tertiary-care hospital, covering pre-, during, and post-COVID-19 years. Overall, 80 of 826 patients (9.7%) tested positive for B19V DNA. A significant increase in positivity was observed in 2024 (23.4%), with a peak in May, representing an eightfold rise compared to 2019–2020. Despite this surge, the distribution of positive cases across population categories remained consistent with previous years, with 32 of 80 (40.0%) positive samples from pregnant women and 27 of 80 (33.8%) from hematology/oncology patients. Among 66 B19V DNA-positive patients with available serology, 4 of 66 (6.1%)—all immunocompromised—lacked detectable IgM/IgG despite high B19V DNA levels (7.8 log10 IU/mL). These findings highlight the importance of integrating molecular and serological diagnostics, particularly in high-risk populations. Given the potential impact of the COVID-19 pandemic on B19V circulation, continued surveillance is essential to determine whether this resurgence represents a temporary fluctuation or a sustained epidemiological shift.